The Oxford history of music vol. IV: the age of Bach & Handel - Fuller Maitland, John Alexander 1856-1936 (Oxford Clarendon Press, 1902)
Excerpt from The Oxford History of Music, Vol. 4: The Age of Bach and HandelBoth, however, may justly be regarded as the epitomes of the period in which they lived; it is true Of each, but in very widely different senses, that he embodied in himself the whole of the music Of his age. For Handel, the older composers and his own contemporaries existed as a treasure-house from which he might appropriate the ideas he was too busy to invent for himself; the circumstances of his career made him acquainted with the styles of all countries, and nearly all periods, and enabled him to form a style in which could be assimilated with equal success his own inventions and his adaptations from other men. Bach, with a far narrower range of musical literature at his command for purposes of study, entered far more deeply into the spirit of those he knew, and, grasping the essential principles upon which the Older masters had worked, rather than the external features of their work, be attained to a style entirely his own, a style which in some points has never been superseded in all the years that have passed since his death.